The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1158/1078-0432.ccr-14-2332
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin System Inhibitors and Survival Outcomes in Patients with Metastatic Renal Cell Carcinoma

Abstract: Purpose: The renin-angiotensin system may play a role in carcinogenesis. The purpose of this study was to evaluate the impact of angiotensin system inhibitors (ASI) on outcomes in metastatic renal cell carcinoma (mRCC) patients treated in the targeted therapy era.Experimental Design: We conducted a pooled analysis of mRCC patients treated on phase II and III clinical trials. Statistical analyses were performed using Cox regression adjusted for several risk factors and the Kaplan-Meier method.Results Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 39 publications
7
86
1
1
Order By: Relevance
“…The current study did not support a protective effect for ASI in ccRCC (Tables 4 and 5). However, other studies have found that ASIs may offer survival benefits in kidney cancer in the targeted treatment era [11, 27]. Possibilities for this discrepancy include insufficient power in the current study to detect a benefit from ASIs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The current study did not support a protective effect for ASI in ccRCC (Tables 4 and 5). However, other studies have found that ASIs may offer survival benefits in kidney cancer in the targeted treatment era [11, 27]. Possibilities for this discrepancy include insufficient power in the current study to detect a benefit from ASIs.…”
Section: Discussionmentioning
confidence: 62%
“…However, further clinical description, for example the anatomic metastatic pattern, of these patient cohorts is lacking. Furthermore, while evidence emerges that comorbidities and their treatment may influence kidney cancer outcomes [10, 11], the distribution of these among ccA and ccB patients remain to be addressed. These are analyses which may prove important in understanding the biology and clinical relevance of these ccRCC molecular subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…If antihypertensive agents are required to control high BP, treatment guidance (e.g., European Society of Cardiology guidelines) [52] should be followed. However, angiotensin system inhibitors may now be the treatment of choice, following analyses of data from Izzedine et al [53] and McKay et al [54] showing that concomitant use of angiotensin system inhibitors is associated with significant improvements in survival outcomes in patients with mRCC. Dose escalation is currently not recommended if a patient is already hypertensive/taking antihypertensive medication according to the axitinib summary of product characteristics [13], but frequently occurs (with appropriate monitoring and treatment) in real-world clinical practice.…”
Section: Proactive Management Of Aesmentioning
confidence: 99%
“…proteinuria, could further enhance the predictive role of hypertension. Moreover, there is early evidence that the use of specific blood pressure lowering drugs might improve cancer outcomes in patients receiving anti-VEGF drugs [32]. Potential interactions between blood pressure lowering drugs and specific anti-VEGF drugs might be relevant in this context [33].…”
Section: Anti-vegf-induced Hypertension and Cancer Outcomes: Translatmentioning
confidence: 99%